The Influence of Shopping Lifestyle and Hedonic Motivation on Blibli Impulse Buying - Amellia Putri; Dorothy Rouly H. Pandjaitan; Nuzul Inas Nabila (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The quick expansion of e-commerce has changed how consumers make purchases and made impulsive purchases more common in online shopping settings. Blibli, one of the top local e-commerce sites in Indonesia, provides a range of features, sales, and shopping experiences that can encourage customers to make impulsive purchases. The purpose of this study is to investigate how Blibli customers in Bandar Lampung's shopping lifestyle and hedonic purchasing motivation affect impulsive purchases. Using primary data gathered from questionnaires given to 115 respondents chosen by purposive sampling, a quantitative research approach with an associative causal design was used. Multiple linear regression was used to analyze the data using IBM SPSS 26. According to the findings, people who consider shopping to be an integral part of their lifestyle are more likely to make impulsive purchases. Additionally, hedonic shopping motive was found to have a favorable and significant impact on impulse buying, indicating that customers who shop for pleasure, amusement, and emotional fulfillment are more likely to make impulsive purchases. Additionally, 53.8% of the difference in impulsive purchasing behavior was explained by the two independent factors taken together. The study comes to the conclusion that among Bandar Lampung Blibli customers, hedonic purchasing motivation and shopping lifestyle are significant predictors of impulsive purchases.